Spatial Differentiation and Market Power in Input Procurement: Evidence from a Structural Model of the Corn Market - Jinho Jung; Juan Sesmero; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2020)
We estimate the cost of transporting corn and the resulting degree of spatial differentiation among downstream firms that buy corn from upstream farmers and examine whether such differentiation softens competition enabling buyers to exert market power (defined as the ability to pay a price for corn that is below its marginal value product net of processing cost). We estimate a structural model of spatial competition using corn procurement data from the U.S. state of Indiana from 2004 to 2014. We adopt a strategy that allows us to estimate firm-level structural parameters while using aggregate data. Our results return a transportation cost of 0.12 per bushel per mile (5% of the corn price under average distance traveled), which provides evidence of spatial differentiation among buyers. The estimated average markdown is 0.80 per bushel (16% of the average corn price in the sample), of which 0.34 is explained by spatial differentiation and the rest by the fact that firms operated under binding capacity constraints. We also find that corn prices paid to farmers at the mill gate are independent of distance between the plant and the farm, providing evidence that firms do not engage in spatial price discrimination. Finally, we evaluate the effect of hypothetical mergers on input markets and farm surplus. A merger between nearby ethanol producers eases competition, increases markdowns by 20%, and triggers a sizable reduction in farm surplus. In contrast, a merger between distant buyers has little effect on competition and markdowns.
Keywords: D43; L11; L13; L43; Q11; Q13; 330; corn procurement; transportation costs; spatial differentiation; buyer power; spatial price discrimination; merger